Perspectives on Enhanced Measurement-Based Care Among Healthcare Providers, Adults, Adolescent Patients with Major Depressive Disorder and Pediatric Family Members: A Multicenter Online Investigation - Zhang H; Sun P; Wang X; Yang X; He Y; Yang T; Su Y; Fu Y; Li Q; Sun J; Liu J; Murphy JK; et al. (Neuropsychiatric Disease and Treatment)
Haonan Zhang,1,* Ping Sun,2,* Xing Wang,1 Xiaorui Yang,3 Yuru He,1 Tao Yang,1 Yousong Su,1 Yi Fu,4 Qingwei Li,4 Jinhua Sun,5 Jing Liu,6 Jill K Murphy,6 Erin E Michalak,6 Raymond W Lam,6 Jun Chen,1 Yiru Fang1,7– 9 1Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Qingdao Mental Health Center, Qingdao, Shandong, People’s Republic of China; 3Shanghai Sixth People’s Hospital Affiliated to Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 4Department of Psychiatry, Tongji Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China; 5Department of Psychiatry and Psychology, Children’s Hospital of Fudan University, National Children’s Medical Center, Shanghai, People’s Republic of China; 6University of British Columbia, Department of Psychiatry, Vancouver, British Columbia, Canada; 7Department of Psychiatry & Affective Disorders Center, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 8CAS Center for Excellence in Brain Science and Intelligence Technology, Shanghai, People’s Republic of China; 9Shanghai Key Laboratory of Psychotic Disorders, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Chen, Clinical Research Center, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Xuhui District, Shanghai, 200030, People’s Republic of China, Email doctorcj2010@gmail.com Yiru Fang, Department of Psychiatry & Affective Disorders Center, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Huangpu District, Shanghai, 200025, People’s Republic of China, Email yirufang@aliyun.comObjective: Measurement-based care (MBC) is an emerging, objective, and systematic evidence-based practice for monitoring symptom severity and treatment efficacy to assist clinicians in developing individualized treatment strategies for patients with major depressive disorder (MDD). This study aimed to identify the barriers and facilitators of enhanced MBC (eMBC) in the outpatient setting to clarify the eMBC utilization dilemma.Methods: Between September 2022 and June 2023, we collected the opinions of healthcare providers, adult and adolescent patients, and family members of adolescent patients via online surveys. Specifically, we surveyed their acceptance and perspectives on MBC and eMBC primarily through custom-designed Likert scales developed for this study.Results: We received responses from 270 adult patients, 144 adolescent patients, 109 family members, and 355 healthcare providers. The results showed that 85.3% of patients and family members were willing to use the eMBC intervention. However, adolescent patients responded significantly differently from the other two groups, with lower acceptance and confidence. Among healthcare providers, while only 69.9% used MBC in practice, 94% believed standardized scales would be effective in treatment, and 91.8% were willing to try eMBC. Additionally, we received 277 remarks regarding eMBC from patients and families.Conclusion: In general, both clinicians and patients looked forward to using eMBC and recognized the potential benefits. However, they still had many concerns about privacy, professionalism, and time consumption. Responses from adolescent patients appeared more conservative and lacked confidence in eMBC. Further implementations are required to explore how eMBC can be operationalized in the outpatient setting to help different patients.Keywords: measurement-based care, enhanced measurement-based care, major depressive disorder, digital health, implementation, treatment